Analisis faktor-faktor yang mempengaruhi utang luar negeri Indonesia - Reza Fahlepi; Syaparuddin Syaparuddin (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
The purpose of this study is to (1) see the description of Indonesia's foreign debt, saving-investment gap, current account balance, and the budget deficit for the period 1990-2016. (2) analyze the effect of the saving-investment gap, current account balance, and budget deficit on Indonesia's foreign debt. The method used in this research is descriptive quantitative analysis with multiple regression model analysis using the Ordinary Least Square (OLS) method. The results of this research are the average development of Indonesia's foreign debt is 6.21 percent, the Saving-Investment gap is 12.47 percent, the current account balance is 394.19 percent, and the budget deficit is 60.91 percent. Based on the analysis results, the Saving-Investment gap and budget deficit have a positive and significant effect on foreign debt. In contrast, the current account balance has a negative and insignificant effect on foreign debt, with a coefficient of determination of 85.52 percent. Keywords: Foreign debt, Saving-investment gap, Current account, Budget deficit